SEARCH FOR THE DECAY K(S)-]PI(0)E+E- - Barr, G; Buchholz, P; Coward, D; Cundy, D; Doble, N; Gatignon, L; Hagelberg, R; Nelson, H; Wahl, H; Peach, K; Blumer, H; Heinz, R; et al. (1993)
The full data set of the experiment NA31 at CERN has been used to search for the decay Ks→π0e+e-. The rate of this decay may be used to determine the magnitude of the state mixing contribution to the CP violating amplitude of the decay KL→π0e+e-. No candidate events for the decayKs→π0e+- were seen. This leads to a branching ratio upper limit of 1.1 × 10-6 at the 90% confidence level. © 1993.